(untitled) (Research, Society and Development, 2021)
The elaboration of the Water Resources Plan is characterized by a process of study, dialogue and continuous consensus, providing a picture of the real situation of Water Resources in different realities and scenarios. In this sense, the objective of this work was to describe the process of social participation in the elaboration of the Water Resources Plan for the Upper Paraguay Basin. Workshops were held where participants were grouped into categories of stakeholders to discuss the challenges and potential applied in the basin. The results demonstrated on the most recurrent themes are related to: basic sanitation, excess of PCH, indiscriminate use of pesticides, overfishing, burning, protection of natural resources, recovery and conservation of springs, ecological tourism model and biodiversity conservation. Although the study identified differences in the representation of social groups, all showed interest in the elaboration of the Water Resources Plan for the Hydrographic Region of Alto Paraguay.